We keep the 2x^2 because we can only subtract something from that if it also is squared. From there, we subtract the 7x from 2x^2-11. Since there is no previous x's in the 2x^2-11, we just make it -7x. So, without even continuing the problem, we see that A) is the correct answer because it is the only one with -7x.
Answer:
Step-by-step explanation:
You can look at it and see that 1/3 is added to each term. The common difference is 1/3. If you want to be be more formal,
d = d4 - d3
d = 0 - - 1/3
d = 0 + 1/3
d = 1/3
Answer:
Option A) One tailed test is a hypothesis test in which rejection region is in one tail of the sampling distribution
Step-by-step explanation:
One Tailed Test:
- A one tailed test is a test that have hypothesis of the form
![H_0: \bar{x} = \mu\\H_A: \bar{x} < \mu\text{ or } \bar{x} > \mu](https://tex.z-dn.net/?f=H_0%3A%20%5Cbar%7Bx%7D%20%3D%20%5Cmu%5C%5CH_A%3A%20%5Cbar%7Bx%7D%20%3C%20%5Cmu%5Ctext%7B%20or%20%7D%20%5Cbar%7Bx%7D%20%3E%20%5Cmu)
- A one-tailed test is a hypothesis test that help us to test whether the sample mean would be higher or lower than the population mean.
- Rejection region is the area for which the null hypothesis is rejected.
- If we perform right tailed hypothesis that is the upper tail hypothesis then the rejection region lies in the right tail after the critical value.
- If we perform left tailed hypothesis that is the lower tail hypothesis then the rejection region lies in the left tail after the critical value.
Thus, for one tailed test,
Option A) One tailed test is a hypothesis test in which rejection region is in one tail of the sampling distribution
Answer:
x=4
Step-by-step explanation:
4x-3=x+9
4x-x-3=9
4x-x=9+3
3x=9+3
3x=12
3/3
12/3=4
x=4
Answer:
z = x^3 +1
Step-by-step explanation:
Noting the squared term, it makes sense to substitute for that term:
z = x^3 +1
gives ...
16z^2 -22z -3 = 0 . . . . the quadratic you want
_____
<em>Solutions derived from that substitution</em>
Factoring gives ...
16z^2 -24z +2z -3 = 0
8z(2z -3) +1(2z -3) = 0
(8z +1)(2z -3) = 0
z = -1/8 or 3/2
Then we can find x:
x^3 +1 = -1/8
x^3 = -9/8 . . . . . subtract 1
x = (-1/2)∛9 . . . . . one of the real solutions
__
x^3 +1 = 3/2
x^3 = 1/2 = 4/8 . . . . . . subtract 1
x = (1/2)∛4 . . . . . . the other real solution
The complex solutions will be the two complex cube roots of -9/8 and the two complex cube roots of 1/2.